1997
DOI: 10.1002/(sici)1096-9861(19970526)382:1<89::aid-cne6>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Serial and parallel processing in rhesus monkey auditory cortex

Abstract: Auditory cortex on the exposed supratemporal plane in four anesthetized rhesus monkeys was mapped electrophysiologically with both pure-tone (PT) and broad-band complex sounds. The mapping confirmed the existence of at least three tonotopic areas. Primary auditory cortex, AI, was then aspirated, and the remainder of the cortex on the supratemporal plane was remapped. PT-responses in the caudomedial area, CM, were abolished in all animals but one, in which they were restricted to the high-frequency range. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
70
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(95 citation statements)
references
References 0 publications
22
70
3
Order By: Relevance
“…In the monkey, the primary auditory cortex is subdivided into three fields, A1, R, and RT, which together correspond to the architectonic core and each have primary-like features, including direct thalamic input (ventral medial geniculate nucleus, Rauschecker et al, 1997). The neurons of each field respond to tones over a limited frequency range and are spatially arranged according to preferred frequencies-tonotopy (Brugge and Merzenich, 1973;Morel et al, 1993;Kaas and Hackett, 2000).…”
Section: Introductionsupporting
confidence: 89%
“…In the monkey, the primary auditory cortex is subdivided into three fields, A1, R, and RT, which together correspond to the architectonic core and each have primary-like features, including direct thalamic input (ventral medial geniculate nucleus, Rauschecker et al, 1997). The neurons of each field respond to tones over a limited frequency range and are spatially arranged according to preferred frequencies-tonotopy (Brugge and Merzenich, 1973;Morel et al, 1993;Kaas and Hackett, 2000).…”
Section: Introductionsupporting
confidence: 89%
“…The left AC can discriminate direction of frequency changes only if discrete steps are available for which it shows a fine discrimination, i.e., it seems to develop a directional discrimination from a local perspective of the time-frequency structure of such steps. Thus, our results support the view that auditory patterns are conceptually analyzed-comparable with visual patterns (47,53,(55)(56)(57)(58)-by local (sequential, analytic, relational) processing, preferentially in the left hemisphere, and/or global (parallel, holistic, unitary) processing, preferentially in the right hemisphere (52,53,59). This local/global interpretation should be confirmed by further animal studies, e.g., by experiments testing the smallest gap duration that would be sufficient for sequential processing or by experiments using the same stimuli that must be classified in different ways (44).…”
Section: Discussionmentioning
confidence: 99%
“…Being delivered through a pair of speakers, the tone was perceived at the midline and thus colocalized with the visual stimulus. We opted to use a pure tone stimulus because previous research has shown that core (i.e., primary) auditory cortices respond best to pure tones, whereas belt (i.e., nonprimary) cortices respond best to complex tones and white noise bursts (Rauschecker et al, 1997).…”
Section: Methodsmentioning
confidence: 99%